An end‐to‐end alternative to TCP PEPs: Initial Spreading, a TCP fast start‐up mechanism. (12th March 2015) - Sallantin, Renaud; Baudoin, Cédric; Chaput, Emmanuel; Arnal, Fabrice; Dubois, Emmanuel; Beylot, André‐Luc
Summary: While Transmission Control Protocol (TCP) Performance Enhancing Proxy (PEP) solutions have long been undisputed to solve the inherent satellite problems, the improvement of the regular end‐to‐end TCP congestion avoidance algorithms and the recent emphasis on the PEPs drawbacks have opened the question of the PEPs sustainability. Nevertheless, with a vast majority of Internet connections shorter than ten segments, TCP PEPs continue to be required to counter the poor efficiency of the end‐to‐end TCP start‐up mechanisms. To reduce the PEPs dependency, designing a new fast start‐up TCP mechanism is therefore a major concern. But, while enlarging the Initial Window (IW) up to ten segments is, without any doubt, the fastest solution to deal with a short‐lived connection in an uncongested network, numerous researchers are concerned about the impact of the large initial burst on an already congested network. Based on traffic observations and real experiments, Initial Spreading has been designed to remove those concerns whatever the load and type of networks. It offers performance similar to a large IW in uncongested network and outperforms existing end‐to‐end solutions in congested networks. In this paper, we show that Initial Spreading, taking care of the satellite specificities, is an efficient end‐to‐end alternative to the TCP PEPs. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : While Transmission Control Protocol (TCP) Performance Enhancing Proxy (PEP) solutions have long been undisputed to solve the inherent satellite problems, major flaws have recently been underlined that reopen the question of their sustainability. However, the inefficiency of regular end‐to‐end TCP solutions for the short‐lived connections transmissions prevents their use in the satellite environment. Initial Spreading is an end‐to‐end fast Startup TCP mechanism that outperforms existing end‐to‐end solutions and offers a credible alternative to the TCP PEPs.